2022
DOI: 10.3390/molecules27072089
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Druggable Bioactive Compounds from Catharanthus roseus and Avicennia marina against Colorectal Cancer by Targeting Thymidylate Synthase

Abstract: Colorectal cancer (CRC) is the second most common cause of death worldwide, affecting approximately 1.9 million individuals in 2020. Therapeutics of the disease are not yet available and discovering a novel anticancer drug candidate against the disease is an urgent need. Thymidylate synthase (TS) is an important enzyme and prime precursor for DNA biosynthesis that catalyzes the methylation of deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP) that has emerged as a novel drug target agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The study showed that chicoric acid formed significant interactions with Asp469 while the interaction with nystose is very low. Furthermore, the study utilized molecular dynamics simulation to analyze the protein-ligand complex stability ( Islam et al, 2022 ). Also, MD simulation calculates the RMSD values to confirm the interaction stability and rigidity of the compounds with the target protein ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that chicoric acid formed significant interactions with Asp469 while the interaction with nystose is very low. Furthermore, the study utilized molecular dynamics simulation to analyze the protein-ligand complex stability ( Islam et al, 2022 ). Also, MD simulation calculates the RMSD values to confirm the interaction stability and rigidity of the compounds with the target protein ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-aza-dc was selected as a positive control for DNMT proteins. The proteins were preprocessed using Biovia Discovery Studio visualizer (3ds.com/products-services/biovia/products/molecular-modeling-simulation/biovia-discovery-studio/visualization/) version (16.1.0) ( 41 ). For molecular docking, PyRX software version 0.8 ( ) ( 42 ) was used via integrated Open Bable to optimize ligands.…”
Section: Methodsmentioning
confidence: 99%
“…Autodock wizards were used to create maximum grid box dimensions. After running docking via Run Autodock in Vina wizard, the ligand in a complex with the protein was visualized using Biovia Discovery Studio visualizer version (16.1.0) ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immuno-oncology is the newest field of research in this area and its scope and full potential are yet to be explored. As part of immunotherapy, specific parts of the patient’s immune system are used to treat a range of diseases, including cancer and mostly solid tumors [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Cancer immunotherapy aims to re-activate the immune system, which has been suppressed by tumor cells in numerous ways.…”
Section: Introductionmentioning
confidence: 99%